Penerapan Metode Reward Teknik Token Economy Untuk Meningkatkan Minat Belajar Anak di TK Melati Desa Air Rupik - Dwi Hurriyati; Natallija Butar Butar; Desy Arisandy (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2022)
Kindergarten education is very important because it is a golden age for children to learn things that will determine their future. This must be supported by appropriate learning methods to support children's learning success. One of them is by applying the token economy technique. The purpose of this service is to increase interest in learning for TK Melati’s children. This service uses an experimental approach by applying the token economy technique. The results of this service indicate an increase in feelings of enjoyment, involvement, enthusiasm, and attentiveness in children during learning activities. Thus, it can be concluded that there is an increase in the interest in learning of TK Melati’s children at Desa Air Rupik through the application of token economy techniques